On Christ and Healing: Eiesland, Tillich, and Disability Theology - Wilder, Courtney (Dialog, 2012)
The existentialist interpretation of the biblical texts offered by Protestant theologian Paul Tillich is deeply problematic in its treatment of disability, especially mental illness. Theologian Nancy Eiesland argues against a conflation of sin and illness, and proposes the symbol of the disabled God as a source for a liberation theology of disability. Reading the biblical texts existentially, as Tillich suggests, can advance Eiesland's Christology, while her critique of Christian teaching on disability offers a correction for Tillich.